Development and Analytical Validation of a Reverse Transcription Droplet Digital PCR (RT-ddPCR) Assay for PD-L1 Transcripts in Circulating Tumor Cells. (9th January 2021) - Strati, Areti; Zavridou, Martha; Economopoulou, Panagiota; Gkolfinopoulos, Stavros; Psyrri, Amanda; Lianidou, Evi
Abstract: Background: PD-L1, an immune checkpoint protein, is an important biomarker for monitoring cancer patients during the administration of cancer immunotherapy. Droplet digital PCR (ddPCR), is a highly sensitive and accurate tool for the quantification of cancer biomarkers in liquid biopsy. We report the development and analytical validation of a novel duplex RT-ddPCR assay for the simultaneous quantification of PD-L1 and hypoxanthine phosphoribosyltransferase ( HPRT ) (used as reference gene) transcripts in circulating tumor cells (CTCs). Methods: RT-ddPCR experimental conditions were first optimized and the assay was analytically validated using synthetic standards and the BB49 and SCC47 cancer cell lines. The developed assay was further applied in 71 peripheral blood (PB) samples from head and neck squamous cell carcinoma (HNSCC) patients and 20 PB samples from healthy donors. PD-L1 and HPRT transcripts were quantified in cDNAs derived from CTCs isolated by a size-dependent microfluidic device. The developed RT-ddPCR assay was directly compared to RT-qPCR using 71 identical patient cDNA samples. Results: Analytical sensitivity was 0.64 copies/μL, while estimation of intra- and interassay variation revealed a high reproducibility (within-run CV%:4.7–23%; between-run CV%:13%). Using the developed RT-ddPCR assay 33/71(46.5%) HNSCC patients' samples were found positive for PD-L1 expression in CTCs, while by using RT-qPCR fewer samples (23/71, 32.4%) were positive (concordance: 55/71, 77.5%). Conclusions: The developed RT-ddPCR assay for PD-L1 in CTCs is highly sensitive, specific, and reproducible; additionally, it offers improved diagnostic sensitivity over RT-qPCR. The clinical utility of the assay should be prospectively evaluated for the real-time monitoring of CTCs of cancer patients under immunotherapy.